RENCANA BISNIS MOCAFFE CAKE SHOP - , Titis Bekti Utami ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Wheat is one of the many food items needed by domestic consumers and the food industry in Indonesia. From the data in the agriculture ministry, Indonesia imported 680.12 thousand tons of wheat flour in 2011 and spent foreign exchange amounting to U.S. $281,757,606. This condition, when repeatedly done, will cause some problems. Indonesian people's dependence on wheat has caused problems in the food security system in Indonesia because of the whole wheat flour in Indonesia needs come from imports. Mocaf flour (modified cassava flour) is cassava flour that has been modified by treatment with fermentation, so that the resulting cassava flour has similar characteristics that can be used as a substitute for wheat flour or a mixture of 30 % - 100 %. One of the products that can be processed by using mocaf is cake. This research uses descriptive qualitative method to describe the business processes and cakes characteristics used as a basis for carrying out business activities in the future. The data used are primary data and secondary data. Primary data came from questionnaires, surveys and observations. The survey was conducted to cake entrepreneurs in Yogyakarta region, to get an idea of cake consumption in Yogyakarta area. Secondary data are taken from the internet and articles on the theory of business plan and cake business overview. Analysis conducted are the industry analysis and functional analysis including analysis of marketing, operations analysis, human resources analysis, and financial analysis. The analysis of the Mocaffe Cake Shop business financial calculation showed very positive results. In the most likely scenario, the initial investment was Rp 845.206.000,00 NPV obtained was Rp.4.484.027,38 IRR was 157 %. Based on the calculation, Mocaffe Cake Shop business is generating positive NPV value. That way, after taking into account the value of the probability of most likely scenario, the investment plan is financially viable and feasible to run.